2021
DOI: 10.7759/cureus.13143
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Attendances to a Minor Injury Department During a Pandemic

Abstract: Introduction: As coronavirus disease 2019 (COVID-19) became a public health emergency of international concern, countries across the globe began to instate strict social distancing restrictions or “lockdowns”. During these times emergency departments in the United Kingdom (UK) recorded a significant drop in patients attending when compared to the same months of previous years. Attendances related to musculoskeletal (MSK) trauma also saw a significant drop in numbers Objective: The purpose of this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 25 publications
2
11
1
Order By: Relevance
“…The duration of symptoms before admission was longer than in previous years but the difference was not significant. Our conclusions are confirmed by data from the United Kingdom and Italy, where a significant drop in attendances at HED in both children and adults due to musculoskeletal pain was observed during pandemic [32,33]. Some reports present neurological and musculoskeletal symptoms in patients with COVID-19, including myalgia (19% ) and back pain (10%) [34].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The duration of symptoms before admission was longer than in previous years but the difference was not significant. Our conclusions are confirmed by data from the United Kingdom and Italy, where a significant drop in attendances at HED in both children and adults due to musculoskeletal pain was observed during pandemic [32,33]. Some reports present neurological and musculoskeletal symptoms in patients with COVID-19, including myalgia (19% ) and back pain (10%) [34].…”
Section: Discussionsupporting
confidence: 84%
“…To our knowledge, none of the published studies have provided separate data on children with musculoskeletal pain in HED during the COVID-19 pandemic, although for adults or collective were presented [31][32][33]. During the pandemic fewer patients with musculoskeletal pain reported to our HED.…”
Section: Discussionmentioning
confidence: 96%
“…5 Some studies have specifically looked at ER encounters related to MSK health conditions during the pandemic and reported a reduction in the total number of encounters. [6][7][8] This decline ranged between 45.4% and 86.1% when compared with the same time period in the calendar year 2019.…”
mentioning
confidence: 82%
“…A smaller study conducted in an ER in the United Kingdom showed an overall 45.4% reduction in attendance during the lockdown in 2020 when compared to 2019, including a reduction of 58.9% and 78.5% of patients in patients presenting with back pain and neck pain, respectively. 7 The mean age of the patients increased by 5 years, and the number of encounters associated with road accidents was reduced from 70 to 8. Another large study conducted in a large trauma center in France also reported a reduction (52.1%) in MSK encounters in the ER.…”
Section: Musculoskeletal Encountersmentioning
confidence: 99%
“…Re-deployed referral patterns changed during COVID because patients with certain hand injuries increased as more patients fell while cycling or were injured in DIY-related accidents [6,8]. Practices evolved to adapt to non-operative management pathways by using Fluoroscan (Hologic, Inc., Marlborough, MA) in the hand clinic without compromising the standard of care by manipulating more fractures in outpatients rather than main theatres or day-case facilities.…”
Section: Introductionmentioning
confidence: 99%